2017
DOI: 10.25141/2474-8811-2017-4.0010
|View full text |Cite
|
Sign up to set email alerts
|

Coding By Quantum Entanglement Entropy

Abstract: Research ArticleOpen Access ISSN 2474-8811 Coding By Quantum Entanglement Entropy In our view, the Universe can be described as having two forms of energy: one related to attractive gravitational forces, which is negative, and the other related to mass according to Einstein's formula E = mc , which is positive. The generation of nonequilibrium structures (such as Bénard vortices or chemical oscillations), where energy is conserved, also corresponds to a free lunch, for the price of nonequilibrium structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…According to 2014 research from Channel 4's Dispatches and The Institute for Global Food Security, around 58 per cent of ricebased products in the UK contained high levels of arsenic. However, new legal limits were introduced last year by the EU in response to safety concerns [2,18].…”
Section: The Unusual Methods Of Cooking Rice Traces the Poison Arsenicmentioning
confidence: 99%
See 2 more Smart Citations
“…According to 2014 research from Channel 4's Dispatches and The Institute for Global Food Security, around 58 per cent of ricebased products in the UK contained high levels of arsenic. However, new legal limits were introduced last year by the EU in response to safety concerns [2,18].…”
Section: The Unusual Methods Of Cooking Rice Traces the Poison Arsenicmentioning
confidence: 99%
“…Another recent study also showed that dieters who ate fewer than 40 grams of carbohydrates per day lost about 8 pounds more than dieters who were put on a low-fat diet. Several other studies have shown that high -carb diets may be the real heart-disease culprit, not only saturated fat [2].…”
Section: The Best Diet According To Harvard Researchersmentioning
confidence: 97%
See 1 more Smart Citation
“…This technique could allow more flexibility in choosing two-photon sources for quantum optics applications. We can consider two photons in two optical modes, such as two polarization, two propagation directions, or two waveguide modes [4][5][6][7].…”
Section: The Spatiotemporal Entanglement Evolution In Free Spacementioning
confidence: 99%
“…High expression of Jagged-1 is correlated with the recurrence of prostate cancer, etc. Moreover, inhibiting Notch signaling with -secretase (GSI) in rodents caused an overproduction of goblet and enteroendocrine cells [15].…”
Section: Notch Protein As Leading Cause Of World Cancer Epidemicmentioning
confidence: 99%